Pengelolaan Keuangan Dan Strategi Pemasaran Dalam Usaha Mikro Kecil Dan Menengah (Studi Kasus Pada Azhar Abdullah Tenun Songket Di Kabupaten Batu Bara) - Elvira Yanti Ahmad; Yenni Samri Juliati Nasution; Nurwani Nurwani (Journal on Education, 2023)
This study aims to determine the financial management and marketing strategies implemented by Azhar Abdullah songket weaving micro, small and medium enterprises (MSMEs) in Batu Bara District. This research is a qualitative descriptive study using primary data. Interview and documentation data collection techniques. The subject of this research is the owner of a micro, small and medium enterprise (MSMEs), Mr. Azhar Abdullah. The results of this study indicate that Azhar Abdullah songket weaving in his financial management has not implemented good financial management which consists of planning, recording, reporting and controlling. Whereas in the marketing strategy, the products produced are of high quality and quality, prices are in accordance with quality, distribution places are easy to reach, but have not carried out promotions on social media